Determination of adjustment parameters for continuous centerless grinding operations - Malinin, P.V.; Bochkarev, P.Yu; Artemov, I.I.; Goncharov, M.O. (Известия высших учебных заведений. Поволжский регион:Технические науки, 2023)
Background. The use of centerless grinding methods in modern production systems, despite their high productivity, is hindered for reasons related to insufficient scientific study of the issues of their technological preparation. First of all, this applies to design procedures at the stages of equipment commissioning and its adjustment during the implementation of operations. Materials and methods. Studies are presented that allow developing methodological approaches and creating models for determining adjustment parameters when performing centerless grinding operations. Their difference from the known ones lies in taking into account the contact points of the treated surface and the elements of the technological system that are constantly changing during processing. The spatial location of the contact points in the working area determines the circuit of the power closure of the centerless grinding and is a determining factor in ensuring the quality of processing. Results. Dependences are derived that allow, based on the established dimensional relationships between the tuning parameters and the characteristics of the grinding and driving wheels, the plane of the support knife, to determine the contact points in all cross-sections in the processing zone. Verification of the developed dependencies allowed us to confirm their operability and improve the quality of work during equipment commissioning. Conclusions. The models described in the article expand the formalized component of the methodological support of technological training and are a necessary link in the creation of an automated planning system for operations performed on centerless grinding equipment.